Hotspot DAXX, PTCH2 and CYFIP2 mutations in pancreatic neuroendocrine neoplasms. Issue 1 (January 2019) - Vandamme, T; Beyens, M; Boons, G; Schepers, A; Kamp, K; Biermann, K; Pauwels, P; De Herder, W W; Hofland, L J; Peeters, M; Van Camp, G; Op de Beeck, K
Abstract : Mutations in DAXX/ATRX, MEN1 and genes involved in the phosphoinositide-3-kinase/Akt/mammalian target of rapamycin (PI3K/Akt/mTOR) pathway have been implicated in pancreatic neuroendocrine neoplasms (pNENs). However, mainly mutations present in the majority of tumor cells have been identified, while proliferation-driving mutations could be present only in small fractions of the tumor. This study aims to identify high- and low-abundance mutations in pNENs using ultra-deep targeted resequencing. Formalin-fixed paraffin-embedded matched tumor-normal tissue of 38 well-differentiated pNENs was sequenced using a HaloPlex targeted resequencing panel. Novel amplicon-based algorithms were used to identify both single nucleotide variants (SNVs) and insertion-deletions (indels) present in >10% of reads (high abundance) and in <10% of reads (low abundance). Found variants were validated by Sanger sequencing. Sequencing resulted in 416, 711, 794 reads with an average target base coverage of 2663 ± 1476. Across all samples, 32 high-abundance somatic, 3 germline and 30 low-abundance mutations were withheld after filtering and validation. Overall, 92% of high-abundance and 84% of low-abundance mutations were predicted to be protein damaging. Frequently, mutated genes were MEN1, DAXX, ATRX, TSC2, PI3K/Akt/mTOR and MAPK-ERK pathway-related genes. Additionally, recurrent alterations on the same genomic position, so-called hotspot mutations, were found in DAXX, PTCH2 and CYFIP2 . This first ultra-deep sequencing study highlighted genetic intra-tumor heterogeneity in pNEN, by the presence of low-abundance mutations. The importance of the ATRX/DAXX pathway was confirmed by the first-ever pNEN-specific protein-damaging hotspot mutation in DAXX. In this study, both novel genes, including the pro-apoptotic CYFIP2 gene and hedgehog signaling PTCH2, and novel pathways, such as the MAPK-ERK pathway, were implicated in pNEN.